Gallium arsenide semiconductor parameters extracted from pin diode measurements and simulations. Issue 4 (1st March 2016) - Bhojani, Riteshkumar; Kowalsky, Jens; Simon, Tom; Lutz, Josef
Abstract : To understand the functioning of the gallium arsenide (GaAs) pin diode and to allow predictive simulations it is essential to have knowledge of the underlying physics. The GaAs pin diode is described with the help of experimental and simulation results. The static characteristics of 15 A – 600 V GaAs pin diodes were measured at ambient and elevated temperature. A quasi‐one‐dimensional simulation model was designed and compared with experimentally measured results. The surge current behaviour was investigated for GaAs pin diodes at two different temperatures. A thermal simulation was performed to give an overview over temperature distribution inside the GaAs pin diode. Several important physical device models and various parametric data were incorporated for theoretical investigation of these diodes. Good agreement between experimental and simulated results of GaAs pin diodes was found at all temperatures.